Wage pattern and livelihood of Tea garden laborer : a study on Loobacherra Tea Estate, Kanaighat, Sylhet, Bangladesh - Hossain, SM. Sohrab (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2015.